Painful temporomandibular joint overloading induces structural remodeling in the pericellular matrix of that joint's chondrocytes. Issue 2 (27th April 2021) - Franklin, Melissa; Sperry, Megan M.; Phillips, Evan; Granquist, Eric J.; Marcolongo, Michele; Winkelstein, Beth A.
Abstract: Mechanical stress to the temporomandibular joint (TMJ) is an important factor in cartilage degeneration, with both clinical and preclinical studies suggesting that repeated TMJ overloading could contribute to pain, inflammation, and/or structural damage in the joint. However, the relationship between pain severity and early signs of cartilage matrix microstructural dysregulation is not understood, limiting the advancement of diagnoses and treatments for temporomandibular joint‐osteoarthritis (TMJ‐OA). Changes in the pericellular matrix (PCM) surrounding chondrocytes may be early indicators of OA. A rat model of TMJ pain induced by repeated jaw loading (1 h/day for 7 days) was used to compare the extent of PCM modulation for different loading magnitudes with distinct pain profiles (3.5N—persistent pain, 2N—resolving pain, or unloaded controls—no pain) and macrostructural changes previously indicated by Mankin scoring. Expression of PCM structural molecules, collagen VI and aggrecan NITEGE neo‐epitope, were evaluated at Day 15 by immunohistochemistry within TMJ fibrocartilage and compared between pain conditions. Pericellular collagen VI levels increased at Day 15 in both the 2N ( p  = 0.003) and 3.5N ( p  = 0.042) conditions compared to unloaded controls. PCM width expanded to a similar extent for both loading conditions at Day 15 (2N, p  < 0.001; 3.5N, p  = 0.002). Neo‐epitope expression increased in the 3.5N group over levels in the 2N group ( p  = 0.041), indicating pericellular changes that were not identified in the same groups by Mankin scoring of the pericellular region. Although remodeling occurs in both pain conditions, the presence of pericellular catabolic neo‐epitopes may be involved in the macrostructural changes and behavioral sensitivity observed in persistent TMJ pain. Abstract : The pericellular matrix (PCM) reorganizes following repeated temporomandibular joint (TMJ) overloading in a rat model with tunable pain conditions. There is subtle expansion of pericellular width, and increased expression of aggrecan neo‐epitope and collagen VI. Collagen VI increases independent of loading magnitude whereas aggrecan fragmentation increases upon greater loading. Here, we characterize the dynamic microenvironment of the PCM and begin to bridge the complex relationships between pain, cartilage biochemical changes, and structural degradation representative of progressive TMJ‐osteoarthritis.